2022
DOI: 10.3389/fimmu.2022.856247
|View full text |Cite
|
Sign up to set email alerts
|

YAP Transcriptional Activity Dictates Cell Response to TNF In Vitro

Abstract: YAP/TAZ are transcription co-factors recently described responsive to pro-inflammatory cytokines and involved in inflammatory-related disorders. However, the role of tumor necrosis factor (TNF), a major pro-inflammatory cytokine, on YAP signaling is not well understood and controversial. Here, we observe in vitro, using wild type and YAP knockout HEK293 cells, that TNF triggers YAP nuclear translocation and transcriptional activity, thus being dependent on Rho family of GTPases. In response to TNF, YAP transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…YAP/TAZ are known to control the expression of actin-related tension proteins MLC2 and DIAPH1, which are important for autophagosome formation 14 . However, we did not evaluate these genes in this work given that we recently showed that MLC2 expression was not detected in HEK293 cells and DIAPH1 expression was similar in HEK293 WT and YAP −/− cells 41 . To confirm the findings of the transcriptional analysis, we monitored autophagic flux in WT, YAP −/− , and YAPΔTEAD −/+ cells.…”
Section: Resultsmentioning
confidence: 99%
“…YAP/TAZ are known to control the expression of actin-related tension proteins MLC2 and DIAPH1, which are important for autophagosome formation 14 . However, we did not evaluate these genes in this work given that we recently showed that MLC2 expression was not detected in HEK293 cells and DIAPH1 expression was similar in HEK293 WT and YAP −/− cells 41 . To confirm the findings of the transcriptional analysis, we monitored autophagic flux in WT, YAP −/− , and YAPΔTEAD −/+ cells.…”
Section: Resultsmentioning
confidence: 99%
“…Crosstalk between innate immune pathways and the Hippo-YAP pathway have been documented previously. The release of inflammatory cytokines, including TNFα, IL-6, and most notably, the inflammasome-generated cytokine IL-1β ( Taniguchi et al, 2015 ; Liu et al, 2020 ; Wang et al, 2020 ; Caire et al, 2022 ), have been shown to stabilize levels of YAP protein and activate its target transcriptional pathways. The effects of activated YAP appear to be cell-type specific.…”
Section: Discussionmentioning
confidence: 99%
“…In tubular epithelial cells, this pathway typically results in cell proliferation and contributes to regeneration of epithelial cells after injury ( Taniguchi et al, 2015 ; Xu et al, 2016 ; Chen et al, 2018 ). Activation of YAP in mononuclear immune cells by inflammatory cytokines appears to promote inflammatory pathways further, including the upregulation of inflammatory cytokines/chemokines ( Liu et al, 2020 ; Caire et al, 2022 ). While it seems likely that the reduced renal levels of YAP and YAP target genes, including Myc, that we show here in female RC/RC: Casp1 KO mice contribute to their suppressed cystic disease, the specific contribution of this pathway to direct effects on tubule cell proliferation or to the inflammatory environment influencing cyst growth has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, phosphorylation of YAP was decreased by the novel ROCK inhibitors. YAP, a member of Hippo signaling pathway, is involved in senescence and regulates proliferation and EMT through TGF-β signaling [ 31 , 32 ]. ROCK drives TEAD/YAP transcription and regulates intracellular tension [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%